건강신념 모델을 적용한 고혈압 영양교육 프로그램 개발 -포커스그룹 인터뷰에 기초하여 - 박서연; 권종숙; 김초일; 이윤나; 김혜경; Park, Seoyun; Kwon, Jong-Sook; Kim, Cho-il; Lee, Yoonna; Kim, Hye-Kyeong (Korean journal of community nutrition, 2012)
Health Belief Model is a socio-psychological theory of decision making to individual health-related behaviors. This study was aimed to develop an effective education program for hypertension based on health belief model. The main factors of health belief model were investigated by focus group interview (FGI) with 23 hypertensive or prehypertensive subjects aged over fifty years. 'Perceived susceptibility' to hypertension was family history, neglect of health care, preference for salty food, broth of soup and stew. Lifelong medication, complications, and medical costs were reported as 'perceived severity' of hypertension. 'Perceived benefits' of hypertension management were decrease of medicinal dose, reduction of medical costs, and healthy eating habits of the family, while 'perceived barriers' were lack of palatability of low salt diet, convenience-oriented dietary habits, and limited choice of foods when eating out. Subjects mentioned TV health programs, public health center programs, and advice from doctors and family as 'cues to action' of hypertension management. These qualitative information provided basis for developing a nutrition education program for hypertension which could be implemented in the public health center. Eight week program was composed of understanding hypertension, risk factor management (eating habits, weight), low salt diet (principles, cooking), advanced management for healthy diet in 2 sessions, and summary. Each session was designed to alert the susceptibility and severity, to emphasize the benefits, and to reduce the barriers by providing dietary monitoring, practical advice, and action tips.